Factors Associated with Decision to Use a Long-Term Intra Uterine Device: A Path Analysis Evidence - Deviasti, Rindra; Pamungkasari, Eti Poncorini; Murti, Bhisma (Journal of Maternal and Child Health, 2018)
Background: Intra uterine device (IUD) is a highly effective contraceptive method with a 98-99 percent success rate over five years of IUD use. However, its share of modern method mix is pitifully small, at less than 5%, in 63 countries and only 5%9% in a further 32 countries. Moreover, IUD's share is declining in many countries. The reasons for this are not well understood, particularly in Mojokerto, East Java, Indonesia, apart from growing popularity of injectables. This study aimed to examine factors associated with decision to use a long-term intra uterine device using a path analysis model.Subjects and Method: A case control study was conducted at Puskesmas (community health center) Gondang, Mojokerto, East Java, from April to May 2018. A sample of 225 women was selected for this study by fixed disease sampling, comprising 75 IUD users and 150 non-IUD users. The dependent variable was IUD use. The independent variables were age, education, knowledge, attitude, self-efficacy, cultural belief, husband support, and peer support. Data on IUD use were taken from puskesmas Gondang. The data were collected by questionnaire and analyzed by path analysis.Results: IUD use was directly and positively associated with positive attitude (b= 0.79; 95% CI= 0.19 to 1.40; p= 0.010) and low anxiety (b= 0.76; 95% CI= 0.16 to 1.37; p= 0.014). IUD use was indirectly associated with cultural belief, self efficacy, education, knowledge, husband support, and peer support.Conclusion: IUD use is directly associated with positive attitude and low anxiety, and is indirectly associated with cultural belief, self efficacy, education, knowledge, husband support, and peer support.Keywords: intra-uterine devise use, biopsychosocial factor, cultural belief, anxietyCorrespondence:Rindra Deviasti. Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami No. 36 A, Surakarta 57126, Central Java. Email: widodarigunung@gmail.com. Mobile: +6281331301065.Journal of Maternal and Child Health (2018), 3(4): 269-277https://doi.org/10.26911/thejmch.2018.03.04.04